A mixed methods examination of patient feedback within forensic and non-forensic mental healthcare services - Mottershead, Trixie (2018)
Background: The literature surrounding patient feedback is limited, despite government policy integrating patient feedback into how the care quality of the National Health Service (NHS) is assessed. Notably, previous literature neglects to examine the detailed contextualised accounts of the service user through qualitative alongside quantitative analysis.